Enchantment in Raul Lino's work. Casa Monsalvat and Casa do Cipreste in Monte Estoril and Sintra (1901-1918) - Pereira, Paulo Manta (Enchantment in Raul Lino's work. Casa Monsalvat and Casa do Cipreste in Monte Estoril and Sintra (1901-1918), 2023)
In the first three quarters of the 20th century, Raul Lino sought in each new synthesis of decorative arts, architecture and urbanism, the total work of art. Heir to his Anglo-Germanic formation, he conceived architecture "from the spoon to the city," like Walter Gropius and those who preceded him in the lineage of William Morris, according to Nikolaus Pevsner (1936). Against the standardisation of production processes, Raul Lino proposed the dense reinterpretation of tradition and used the Portuguese house campaign as a laboratory for a renewal of domestic architecture. He aimed, as he wrote: "to recover the lost harmony of the landscape, of the cities of Portugal". This was the focus of our investigation, with an emphasis on the presence of the marvellous, in the first dozen and a half years of the 20th century. Period marked between the conception of "Monsalvat" house for Alexandre Rey Colaço, in Monte Estoril, and the completion of "Cypress" house, of which he was author and client, in São Pedro de Sintra. … Read more Public File 1